Transcription Factors of CAT1, EFG1, and BCR1 Are Effective in Persister Cells of Candida albicans-Associated HIV-Positive and Chemotherapy Patients - Aboualigalehdari, Elham; Tahmasebi Birgani, Maryam; Fatahinia, Mahnaz; Hosseinzadeh, Mehran (Frontiers in Microbiology, 2021)
Background: Biofilm is an accumulation of cells, which are formed on mucosal surfaces of the host as well as on medical devices. The inherent resistance of Candida strains producing biofilms to antimicrobial agents is an important and key feature for biofilm growth, which can lead to treatment failure. This resistance is due to the regulatory increase of the output pumps, the presence of extracellular matrix and the existence of persister cells. Persister cells are phenotypic variants having MICs similar to antibiotic-sensitive populations and are able to tolerate high doses of antibiotics. The current study investigated the possible role of EFG1, BCR1 and CAT1 in the establishment or maintenance of persister cells in C. albicans strains that produce biofilms. Methods: After identifying Candida isolates by molecular methods, C. albicans isolates were confirmed by sequencing. Isolation of persister cells and determination of their MIC were performed by microdilution method. Then, RNA extraction and cDNA synthesis were performed from 60 C. albicans isolates under promoting and inducing conditions. Afterward, the mean expression of BCR1, EFG1 and CAT1 genes in both persister and non-persister groups was calculated using real time-qPCR. Phylogeny tree of persister and non-persister group isolates was drawn using ITS fragment. Results: A total of 77 persister isolates were taken from the oral cavity of HIV patients as well as from patients undergoing chemotherapy. Biofilm intensity in persister isolates separated from HIV-infected patients was different from the non-persister group. The mean fold change of BCR1 (10.73), CAT1 (15.34) and EFG1 (2.41) genes in persister isolates was significantly higher than these genes in isolates without persister. Conclusion: It can be concluded that the most important factor in the production of persister cells is biofilm binding and production not biofilm development or mature biofilm production, which was found in the expression of BCR1 gene without change in the expression of EFG1 gene in the persister group. Also, catalase plays an essential role in the production of persister in C. albicans biofilm producers with ROS detoxification.